Efektifitas Smile Education Terhadap Tingkat Kecemasan Remaja Putri dalam Menghadapi Menarche - Khusnul Hatimah; Sri Wahyuni; Apriliani Yulianti Wuriningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
For girls, menarche was the first time they had their period, which was marked by changes in their bodies and minds. Several things can make teenage girls anxious, and one of them is that they don't know enough about menstruation. This means that when they hit puberty, they aren't ready and don't know what to do. Our study's goal is to find out how well smile education reduces the stress that teenage girls feel as they approach menarche at SD Islam Sultan Agung 01 Semarang and SD Islam Sultan Agung 04 Semarang. This research is a type of quasi-experimental research with a control group design with two groups: one before the test and one after the test. The sample was made up of 156 people. A proportionate stratified random sample method was used, and a questionnaire was used as a study tool. The Wilcoxon Sign Rank test and the Mann Whitney test are used in this work. The Wilcoxon test showed that the difference between the pre- and post-tests for the intervention group was 0.000 < 0.05, while the difference for the control group was 0.084 < 0.05. A meaningful number of 0.000 <0.05 was found in the Mann Whitney test. The Wilcoxon pre-post test results of the training group and the control group showed that they were different before and after they learned how to smile. Teenage girls who were getting ready to go through menarche felt less anxious when they used a game-based Smile Education app.